The Importance of Halal Logistics Implementation in Indonesia in Compliance with Domestics and Global Halal Market Requirements - abdul mu'ti sazali; Jeanne Svensky Ligte (Jurnal Transportasi Multimoda, 2019)
Halal logistics is very crucial in ensuring and maintaining halal requirements of halal products from production to consumption. However, the concept of halal logistics is not very well understood and implemented in Indonesia by either the regulators or the logistics players due to a lack of concern from various parties. Therefore, this research is conducted to explain the halal logistics concept, define a potential standard for halal logistics and give recommendations on how the implementation of this concept can be executed in Indonesia, in compliance with domestic and global halal requirements. The methods used in this research are a literature review and a theory analysis, concept and also rules and policies that in force in Indonesia, which in the end can be seen clearly whether halal logistics has been implemented or not to compliance domestic and global markets. The result shows that there is no specific regulation yet in Indonesia in terms of halal logistics and distribution. The authors proposed several recommendations of how to conduct and treat appropriate halal distribution process, which it is expected will be able to be fundamental for the government and MUI to implement and certify it as the regulation standard.